Cancer‐related fatigue: Identification of hallmarks to enable refined treatment approaches. Issue 12 (9th November 2022) - Schmidt, Martina E.; Blickle, Patricia; Steindorf, Karen
Abstract: Objective: Recommendations for fatigue management are commonly given in an undifferentiated manner without further evaluation of patient's specific symptomatology. Thus, we aimed to identify hallmarks of potential fatigue subgroups which might guide more refined treatment. Methods: The FiX study assessed fatigue with the EORTC QLQ‐FA12 in patients around 2 years after cancer diagnosis (T0) including 15 different entities. After 2 years, a follow‐up survey (T1) was conducted. The analyses comprised all patients with prevalent fatigue at T0 ( N = 1023). Hierarchical cluster analysis was performed using the Ward method and including the dichotomized factors emotional distress, pain, insomnia, and obesity. Emotional distress, that is, depressive symptoms and anxiety, was assessed by the PHQ‐4. Pain and insomnia were based on the according symptom scores of the EORTC QLQ‐C30. Analysis of covariance was conducted to investigate the association of the fatigue clusters at T0 with subsequent fatigue at T1. Results: Four hierarchical clusters were identified. The first cluster comprised patients with moderate‐to‐severe distress. The remaining fatigue cases were differentiated by obesity and then by pain. Fatigue cases without any of these three symptoms formed the last cluster. Physical, emotional and cognitive fatigue were highest in the distress cluster. Additionally, this cluster was associated with higher physical, emotional and cognitive fatigue at T1 compared to the other clusters. Conclusions: Fatigue in conjunction with emotional distress had worse impact, persisted longer, and may require other treatment approaches than fatigue in patients without emotional distress. Obesity and pain may be further distinguishing hallmarks for refined fatigue management.